Case Report: Bilateral Epiphysiodesis Due to Extreme Tall Stature in a Girl With a De Novo DNMT3A Variant Associated With Tatton-Brown-Rahman Syndrome - Lennartsson, Otto; Lodefalk, Maria; Wehtje, Henrik; Stattin, Eva-Lena; Sävendahl, Lars; Nilsson, Ola (Frontiers in Endocrinology, 2021)
Objective: To present a rare clinical case of a patient with Tatton-Brown-Rahman syndrome and the outcome of tall stature management with bilateral epiphysiodesis surgery at the distal femur and proximal ends of tibia and fibula. Study design: Clinical case report. Results: This is a 20-year-old female with a history of proportional tall stature, developmental psychomotor and language delay with autism spectrum behavior and distinctive facial features. At 12 years and 2 months of age she was in early puberty and 172.5 cm tall (+ 2.8 SDS) and growing approximately 2 SDS above midparental target height of 173 cm (+ 0.9 SDS). A bone age assessment predicted an adult height of 187.1 cm (+3.4 SDS). To prevent extreme tall stature, bilateral epiphysiodesis surgery was performed at the distal femur and proximal ends of tibia and fibula at the age of 12 years and 9 months. After the surgery her height increased by 12.6 cm to 187.4 cm of which approximately 10.9 cm occurred in the spine whereas leg length increased by only 1.7 cm resulting in a modest increase of sitting height index from 50% (-1 SDS) to 53% (+ 0.5 SDS). Genetic evaluation for tall stature and intellectual disability identified a de novo nonsense variant in the DNMT3A gene previously associated with Tatton-Brown-Rahman syndrome. Conclusion: Tatton-Brown-Rahman syndrome should be considered in children with extreme tall stature and intellectual disability. Percutaneous epiphysiodesis surgery to mitigate extreme tall stature may be considered.